Dorsal root ganglion neurons and tyrosine hydroxylase: An intriguing association with implications for sensation and pain - Brumovsky, Pablo Rodolfo (2016)
Tyrosine hydroxylase (TH) is a rate-limiting enzyme broadly expressed in noradrenergic and dopaminergic neurons in the central nervous system.57,70 Tyrosine hydroxylase is also expressed by peripheral sympathetic neurons98 and by enteric neurons within the gut.81,84 More than 30 years ago, TH was unexpectedly discovered in developing adult rodent cranial and dorsal root ganglion (DRG) neurons. Today, TH-expressing DRG neurons are being rediscovered as a relevant subpopulation. This review addresses the emerging importance of TH-expressing DRG neurons in sensation and pain mechanisms, focusing specifically on (1) their nature as C-low threshold mechanoreceptors (C-LTMRs); (2) their involvement in nociception/pain; and (3) their catecholaminergic phenotype.